(untitled) (Revista Ciência Agronômica, 2020)
Hydration and dehydration cycles during imbibition of seeds may influence their physiological performance, making them more vigorous and resistant to abiotic factors such as water stress. The aim was to investigate whether the times and discontinued hydration cycles condition higher tolerance to water deficiency conditions in germination and seed vigor and accumulation of organic compounds in sorghum seedlings. The experiment was carried out in a randomized experimental design with four replicates of 50 seeds. The treatments were arranged in a 3 × 4 × 6 factorial scheme (hydration times, hydration and dehydration cycles, osmotic potentials). The imbibition curve of the species was determined based on three times (X, Y and Z); and the dehydration curve was constructed. With these times, the seeds were submitted to 0, 1, 2 and 3 cycles of hydration and dehydration (HD). Then, they were submitted to germination test on paper moistened with polyethylene glycol 6000 solution at the osmotic potentials of 0.0 (distilled water), -0.2, -0.4, -0.6, -0.8 and -1.0 MPa. Germination and vigor of sorghum seeds are severely impaired in water potentials equal to or greater than -0.4 MPa. Application of three cycles of hydration and dehydration for a period of 13h in sorghum seeds improves tolerance to water deficiency conditions during germination and seedling development, and provides greater contents of soluble N-amino content and total soluble carbohydrates.